The Effectiveness of Online Zakat Payments: Case Studies in Universities - Ammar Irja Tabah Saputra; Azizah Hafshah Hafsari; Dias Shafa Jauza; Nurul Azmi Julianty (Universitas Pendidikan Indonesia, 2023)
This research focuses on the effectiveness of using zakat online in fulfilling the pillars of Islam. This study also discusses how online zakat platforms can be used effectively in paying zakat to fulfill the pillars of Islam in various ways of outreach to Muslims. The purpose of this study is to find out the Islamic perspective on the use of zakat digitally or online. This study also aims to analyze what online zakat platforms are most often used by the Islamic community in Indonesia. As well as this research also aims to analyze how to socialize zakat online to the public. The research method used is to use quantitative research methods and literature studies. The results of this study are that online zakat is legally valid in the view or perspective of the Islamic religion, but then how can this online zakat be effective in its implementation to fulfill the pillars of Islam and how can this online zakat platform be socialized so that it is known by the Islamic community as one of the forms progresses in the use of technology.